Tetraploid Rangpur lime rootstock increases drought tolerance via enhanced constitutive root abscisic acid production - Allario, Thierry; Brumos, Javier; Colmenero-Flores, José M.; Iglesias, Domingo J.; Pina, José A.; Navarro, Luis; Talón, Manuel; Ollitrault, Patrick; Morillon, Raphael (2017)
Whole-genome duplication, or polyploidy, is common in many plant species and often leads to better adaptation to adverse environmental condition. However, little is known about the physiological and molecular determinants underlying adaptation. We examined the drought tolerance in diploid (2x) and autotetraploid (4x) clones of Rangpur lime (Citrus limonia) rootstocks grafted with 2x Valencia Delta sweet orange (Citrus sinensis) scions, named V/2xRL and V/4xRL, respectively. Physiological experiments to study rootshoot communication associated with gene expression studies in roots and leaves were performed. V/4xRL was much more tolerant to water deficit than V/2xRL. Gene expression analysis in leaves and roots showed that more genes related to the response to water stress were differentially expressed in V/2xRL than in V/4xRL. Prior to the stress, when comparing V/4xRL to V/2xRL, V/4xRL leaves had lower stomatal conductance and greater abscisic acid (ABA) content. In roots, ABA content was higher in V/4xRL and was associated to a greater expression of drought responsive genes, including CsNCED1, a pivotal regulatory gene of ABA biosynthesis. We conclude that tetraploidy modifies the expression of genes in Rangpur lime citrus roots to regulate long-distance ABA signalling and adaptation to stress.